A first search for coincident gravitational waves and high energy neutrinos using LIGO, Virgo and ANTARES data from 2007 - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; Basa, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2013)
We present the results of the first search for gravitational wave bursts associated with high energy neutrinos. Together, these messengers could reveal new, hidden sources that are not observed by conventional photon astronomy, particularly at high energy. Our search uses neutrinos detected by the underwater neutrino telescope ANTARES in its 5 line configuration during the period January - September 2007, which coincided with the fifth and first science runs of LIGO and Virgo, respectively. The LIGO-Virgo data were analysed for candidate gravitational-wave signals coincident in time and direction with the neutrino events. No significant coincident events were observed. We place limits on the density of joint high energy neutrino - gravitational wave emission events in the local universe, and compare them with densities of merger and core-collapse events.
Keywords: gravitational waves / experiments; neutrino astronomy

A method for detection of muon induced electromagnetic showers with the ANTARES detector - Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Auberth, J. J.; Baret, B.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2012)
The primary aim of ANTARES is neutrino astronomy with upward going muons created in charged current muon neutrino interactions in the detector and its surroundings. Downward going muons are background for neutrino searches. These muons are the decay products of cosmic-ray collisions in the Earth's atmosphere far above the detector. This paper presents a method to identify and count electromagnetic showers induced along atmospheric muon tracks with the ANTARES detector. The method is applied to both cosmic muon data and simulations and its applicability to the reconstruction of muon event energies is demonstrated. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Neutrino telescope; Electromagnetic shower identification; High energy muons; Energy reconstruction

Deep-Sea Bioluminescence Blooms after Dense Water Formation at the Ocean Surface - Tamburini, Christian; Canals, Miquel; Houpert, Loic; Lefevre, Dominique; Martini, Verine; D'Ortenzio, Fabrizio; Robert, Anne; Testor, Pierre; Aguilar, Juan Antonio; Al Samarai, Imen; Albert, Arnaud; Andre, Michel; et al. (PLoS ONE, 2013)
The deep ocean is the largest and least known ecosystem on Earth. It hosts numerous pelagic organisms, most of which are able to emit light. Here we present a unique data set consisting of a 2.5-year long record of light emission by deep-sea pelagic organisms, measured from December 2007 to June 2010 at the ANTARES underwater neutrino telescope in the deep NW Mediterranean Sea, jointly with synchronous hydrological records. This is the longest continuous time-series of deep-sea bioluminescence ever recorded. Our record reveals several weeks long, seasonal bioluminescence blooms with light intensity up to two orders of magnitude higher than background values, which correlate to changes in the properties of deep waters. Such changes are triggered by the winter cooling and evaporation experienced by the upper ocean layer in the Gulf of Lion that leads to the formation and subsequent sinking of dense water through a process known as "open-sea convection". It episodically renews the deep water of the study area and conveys fresh organic matter that fuels the deep ecosystems. Luminous bacteria most likely are the main contributors to the observed deep-sea bioluminescence blooms. Our observations demonstrate a consistent and rapid connection between deep open-sea convection and bathypelagic biological activity, as expressed by bioluminescence. In a setting where dense water formation events are likely to decline under global warming scenarios enhancing ocean stratification, in situ observatories become essential as environmental sentinels for the monitoring and understanding of deep-sea ecosystem shifts.

Detection potential of the KM3NeT detector for high-energy neutrinos from the Fermi bubbles - Adrian-Martinez, S.; Ageron, M.; Aguilar, J. A.; Aharonian, F.; Aiello, S.; Albert, A.; Alexandri, M.; Ameli, F.; Anassontzis, E. G.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; et al. (Astroparticle Physics, 2013)
A recent analysis of the Fermi Large Area Telescope data provided evidence for a high-intensity emission of high-energy gamma rays with a E-2 spectrum from two large areas, spanning 50 above and below the Galactic centre (the "Fermi bubbles"). A hadronic mechanism was proposed for this gamma-ray emission making the Fermi bubbles promising source candidates of high-energy neutrino emission. In this work Monte Carlo simulations regarding the detectability of high-energy neutrinos from the Fermi bubbles with the future multi-km(3) neutrino telescope KM3NeT in the Mediterranean Sea are presented. Under the hypothesis that the gamma-ray emission is completely due to hadronic processes, the results indicate that neutrinos from the bubbles could be discovered in about one year of operation, for a neutrino spectrum with a cutoff at 100 TeV and a detector with about 6 km(3) of instrumented volume. The effect of a possible lower cutoff is also considered. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Neutrino telescope; Fermi Bubbles; KM3NeT

Expansion cone for the 3-inch PMTs of the KM3NeT optical modules - Adrian-Martinez, S.; Ageron, M.; Aguilar, J. A.; Aharonian, F.; Aiello, S.; Albert, A.; Alexandri, M.; Ameli, F.; Anassontzis, E. G.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; et al. (Journal of Instrumentation, 2013)
Detection of high-energy neutrinos from distant astrophysical sources will open a new window on the Universe. The detection principle exploits the measurement of Cherenkov light emitted by charged particles resulting from neutrino interactions in the matter containing the telescope. A novel multi-PMT digital optical module (DOM) was developed to contain 31 3-inch photomultiplier tubes (PMTs). In order to maximize the detector sensitivity, each PMT will be surrounded by an expansion cone which collects photons that would otherwise miss the photocathode. Results for various angles of incidence with respect to the PMT surface indicate an increase in collection efficiency by 30% on average for angles up to 45 degrees with respect to the perpendicular. Ray-tracing calculations could reproduce the measurements, allowing to estimate an increase in the overall photocathode sensitivity, integrated over all angles of incidence, by 27% (for a single PMT). Prototype DOMs, being built by the KM3NeT consortium, will be equipped with these expansion cones.
Keywords: Optical detector readout concepts; Instrument optimisation; Cherenkov detectors; Large detector systems for particle and astroparticle physics

First results on dark matter annihilation in the Sun using the ANTARES neutrino telescope - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anton, L.; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; et al. (Journal of Cosmology and Astroparticle Physics, 2013)
A search for high-energy neutrinos coming from the direction of the Sun has been performed using the data recorded by the ANTARES neutrino telescope during 2007 and 2008. The neutrino selection criteria have been chosen to maximize the selection of possible signals produced by the self-annihilation of weakly interacting massive particles accumulated in the centre of the Sun with respect to the atmospheric background. After data unblinding, the number of neutrinos observed towards the Sun was found to be compatible with background expectations. The 90% CL upper limits in terms of spin-dependent and spin-independent WIMP-proton cross-sections are derived and compared to predictions of two supersymmetric models, CMSSM and MSSM-7. The ANTARES limits are comparable with those obtained by other neutrino observatories and are more stringent than those obtained by direct search experiments for the spin-dependent WIMP-proton cross-section in the case of hard self-annihilation channels (W+W-, tau(+)tau(-)).
Keywords: neutrino experiments; dark matter detectors; supersymmetry and cosmology; particle physics - cosmology connection

First search for neutrinos in correlation with gamma-ray bursts with the ANTARES neutrino telescope - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J-J.; Baret, B.; et al. (Journal of Cosmology and Astroparticle Physics, 2013)
A search for neutrino-induced muons in correlation with a selection of 40 gamma-ray bursts that occurred in 2007 has been performed with the ANTARES neutrino telescope. During that period, the detector consisted of 5 detection lines. The ANTARES neutrino telescope is sensitive to TeV-PeV neutrinos that are predicted from gamma-ray bursts. No events were found in correlation with the prompt photon emission of the gamma-ray bursts and upper limits have been placed on the flux and fluence of neutrinos for different models.
Keywords: neutrino experiments; neutrino astronomy; gamma ray bursts theory

FIRST SEARCH FOR POINT SOURCES OF HIGH-ENERGY COSMIC NEUTRINOS WITH THE ANTARES NEUTRINO TELESCOPE - Adrian-Martinez, S.; Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J. -J.; et al. (Astrophysical Journal Letters, 2011)
Results are presented of a search for cosmic sources of high-energy neutrinos with the ANTARES neutrino telescope. The data were collected during 2007 and 2008 using detector configurations containing between 5 and 12 detection lines. The integrated live time of the analyzed data is 304 days. Muon tracks are reconstructed using a likelihood-based algorithm. Studies of the detector timing indicate a median angular resolution of 0.5 +/- 0.1 deg. The neutrino flux sensitivity is 7.5 x 10(-8)(E(v)/GeV)(-2) GeV(-1) s(-1) cm(-2) for the part of the sky that is always visible (delta < -48 deg), which is better than limits obtained by previous experiments. No cosmic neutrino sources have been observed.
Keywords: astroparticle physics; cosmic rays; neutrinos

Measurement of atmospheric neutrino oscillations with the ANTARES neutrino telescope ANTARES Collaboration - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J. -J.; Baret, B.; Basa, S.; et al. (Physics Letters B, 2012)
The data taken with the ANTARES neutrino telescope from 2007 to 2010, a total live time of 863 days, are used to measure the oscillation parameters of atmospheric neutrinos. Muon tracks are reconstructed with energies as low as 20 GeV. Neutrino oscillations will cause a suppression of vertical upgoing muon neutrinos of such energies crossing the Earth. The parameters determining the oscillation of atmospheric neutrinos are extracted by fitting the event rate as a function of the ratio of the estimated neutrino energy and reconstructed flight path through the Earth. Measurement contours of the oscillation parameters in a two-flavour approximation are derived. Assuming maximal mixing, a mass difference of Delta m(32)(2) = (3.1 +/- 0.9) . 10(-3) eV(2) is obtained, in good agreement with the world average value. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Neutrino oscillations; Neutrino telescope; ANTARES

Measurement of the atmospheric nu (mu) energy spectrum from 100 GeV to 200 TeV with the ANTARES telescope - Adrian-Martinez, S.; Albert, A.; Al Samarai, I.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; et al. (European Physical Journal C, 2013)
Atmospheric neutrinos are produced during cascades initiated by the interaction of primary cosmic rays with air nuclei. In this paper, a measurement of the atmospheric energy spectrum in the energy range 0.1-200 TeV is presented, using data collected by the ANTARES underwater neutrino telescope from 2008 to 2011. Overall, the measured flux is similar to 25 % higher than predicted by the conventional neutrino flux, and compatible with the measurements reported in ice. The flux is compatible with a single power-law dependence with spectral index gamma (meas)=3.58 +/- 0.12. With the present statistics the contribution of prompt neutrinos cannot be established.

Measurement of the group velocity of light in sea water at the ANTARES site - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J-J.; Baret, B.; et al. (Astroparticle Physics, 2012)
The group velocity of light has been measured at eight different wavelengths between 385 nm and 532 nm in the Mediterranean Sea at a depth of about 2.2 km with the ANTARES optical beacon systems. A parametrisation of the dependence of the refractive index on wavelength based on the salinity, pressure and temperature of the sea water at the ANTARES site is in good agreement with these measurements. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: ANTARES; Neutrino telescope; Optical beacon system; Velocity of light; Refractive index

SEARCH FOR A CORRELATION BETWEEN ANTARES NEUTRINOS AND PIERRE AUGER OBSERVATORY UHECRs ARRIVAL DIRECTIONS - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; Basa, S.; et al. (Astrophysical Journal, 2013)
A multimessenger analysis optimized for a correlation of arrival directions of ultra-high energy cosmic rays (UHECRs) and neutrinos is presented and applied to 2190 neutrino candidate events detected in 2007-2008 by the ANTARES telescope and 69 UHECRs observed by the Pierre Auger Observatory between 2004 January 1 and 2009 December 31. No significant correlation is observed. Assuming an equal neutrino flux (E-2 energy spectrum) from all UHECR directions, a 90% CL upper limit on the neutrino flux of 5.0 x 10(-8) GeV cm(-2) s(-1) per source is derived.
Keywords: astroparticle physics; cosmic rays; neutrinos

SEARCH FOR COSMIC NEUTRINO POINT SOURCES WITH FOUR YEARS OF DATA FROM THE ANTARES TELESCOPE - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J; Baret, B.; Basa, S.; et al. (Astrophysical Journal, 2012)
In this paper, a time-integrated search for point sources of cosmic neutrinos is presented using the data collected from 2007 to 2010 by the ANTARES neutrino telescope. No statistically significant signal has been found and upper limits on the neutrino flux have been obtained. Assuming an E-nu(-2). spectrum, these flux limits are at 1-10x10(-8) GeV cm(-2) s(-1) for declinations ranging from -90 degrees to 40 degrees. Limits for specific models of RX J1713.7-3946 and Vela X, which include information on the source morphology and spectrum, are also given.
Keywords: astroparticle physics; cosmic rays; neutrinos

Search for neutrino emission from gamma-ray flaring blazars with the ANTARES telescope - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; Basa, S.; et al. (Astroparticle Physics, 2012)
The ANTARES telescope is well-suited to detect neutrinos produced in astrophysical transient sources as it can observe a full hemisphere of the sky at all times with a high duty cycle. Radio-loud active galactic nuclei with jets pointing almost directly towards the observer, the so-called blazars, are particularly attractive potential neutrino point sources. The all-sky monitor LAT on board the Fermi satellite probes the variability of any given gamma-ray bright blazar in the sky on time scales of hours to months. Assuming hadronic models, a strong correlation between the gamma-ray and the neutrino fluxes is expected. Selecting a narrow time window on the assumed neutrino production period can significantly reduce the background.An unbinned method based on the minimization of a likelihood ratio was applied to a subsample of data collected in 2008 (61 days live time). By searching for neutrinos during the high state periods of the AGN light curve, the sensitivity to these sources was improved by about a factor of two with respect to a standard time-integrated point source search. First results on the search for neutrinos associated with ten bright and variable Fermi sources are presented. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: ANTARES; Neutrino astronomy; Fermi LAT transient sources; Time-dependent search; Blazars

Search for relativistic magnetic monopoles with the ANTARES neutrino telescope - Adrian-Martinez, S.; Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J-J.; et al. (Astroparticle Physics, 2012)
Magnetic monopoles are predicted in various unified gauge models and could be produced at intermediate mass scales. Their detection in a neutrino telescope is facilitated by the large amount of light emitted compared to that from muons. This paper reports on a search for upgoing relativistic magnetic monopoles with the ANTARES neutrino telescope using a data set of 116 days of live time taken from December 2007 to December 2008. The one observed event is consistent with the expected atmospheric neutrino and muon background, leading to a 90% C.L. upper limit on the monopole flux between 1.3 x 10-(17) and 8.9 x 10(-17) CM-2 s(-1) sr(-1) for monopoles with velocity beta >= 0.625. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Magnetic monopole; Neutrino telescopes; ANTARES

The ANTARES telescope neutrino alert system - Ageron, M.; Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J. -J.; et al. (Astroparticle Physics, 2012)
The ANTARES telescope has the capability to detect neutrinos produced in astrophysical transient sources. Potential sources include gamma-ray bursts, core collapse supernovae, and flaring active galactic nuclei. To enhance the sensitivity of ANTARES to such sources, a new detection method based on coincident observations of neutrinos and optical signals has been developed. A fast online muon track reconstruction is used to trigger a network of small automatic optical telescopes. Such alerts are generated for special events, such as two or more neutrinos, coincident in time and direction, or single neutrinos of very high energy. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: ANTARES; Neutrino astronomy; Transient sources; Optical follow-up

The positioning system of the ANTARES Neutrino Telescope - Adrian-Martinez, S.; Ageron, M.; Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; et al. (Journal of Instrumentation, 2012)
The ANTARES neutrino telescope, located 40km off the coast of Toulon in the Mediterranean Sea at a mooring depth of about 2475m, consists of twelve detection lines equipped typically with 25 storeys. Every storey carries three optical modules that detect Cherenkov light induced by charged secondary particles (typically muons) coming from neutrino interactions. As these lines are flexible structures fixed to the sea bed and held taut by a buoy, sea currents cause the lines to move and the storeys to rotate. The knowledge of the position of the optical modules with a precision better than 10cm is essential for a good reconstruction of particle tracks. In this paper the ANTARES positioning system is described. It consists of an acoustic positioning system, for distance triangulation, and a compass-tiltmeter system, for the measurement of the orientation and inclination of the storeys. Necessary corrections are discussed and the results of the detector alignment procedure are described.
Keywords: Timing detectors; Detector modelling and simulations II (electric fields; charge transport; multiplication and induction; pulse formation; electron emission; etc); Detector alignment and calibration methods (lasers; sources; particle-beams); Detector control systems (detector and experiment monitoring and slow-control systems; architecture; hardware; algorithms; databases)